2023
DOI: 10.1002/adma.202303341
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Phase‐Transition Entropy into Electrochemical Thermopower and the Peltier Effect

Abstract: A thermocell generates thermopower from a temperature difference (ΔT) between two electrodes. The converse process of thermocells is an electrochemical Peltier effect, which creates a ΔT on the electrodes by applying an external current. The Seebeck coefficient (Se) of the electrochemical system is proportional to the entropy change of the redox reaction; therefore, a redox system having a significant entropy change is expected to increase the Se. In this study, a thermoresponsive polymer having a redox‐active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The NIPAM in the bioderived composite hydrogel sensor is a temperature-sensitive monomer, and the phase transition of the NIPAM occurs at the lower critical solution temperature (LCST), which caused the volume shrinkage of the hydrogel with NIPAM, ,− which can reduce the lattice distance of the photonic crystals and result in a blue shift of the structures (Figure a). Therefore, the sensor can also be used for temperature visualization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The NIPAM in the bioderived composite hydrogel sensor is a temperature-sensitive monomer, and the phase transition of the NIPAM occurs at the lower critical solution temperature (LCST), which caused the volume shrinkage of the hydrogel with NIPAM, ,− which can reduce the lattice distance of the photonic crystals and result in a blue shift of the structures (Figure a). Therefore, the sensor can also be used for temperature visualization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although research in this area remains a frontier, recent examples have demonstrated that synthetic manipulation of the solvation environment serves as a pathway for enhancing DSr and the energy density of the cell. For example, solvent mixtures, 157 the use of dissolved polymers that undergo phase changes upon redox, 158 metallocages that intercalate charge balancing ions through a desolvation process, 159 and polyoxometalate anions 160 all involve large supramolecular changes to solvation structure (Figure 4A). We predict that the ability of solvent to intercalate into pores and the frustration solvent to assemble into ordered shells at porous surfaces will strongly influence the thermoelectrochemical behavior of porous colloids.…”
Section: -4 Implications For Electrochemical Systemsmentioning
confidence: 99%
“…Recent studies include the use of gel-based electrolytes, 12 deep eutectic solvents, 10 and ionic liquids, 13 and materials such as carbon nanotubes for creating thermogalvanic cells that display a high ionic conductivity while retaining a low thermal conductivity, in order to avoid thermal equilibration across the cell. 14 Additionally, the use of solvent mixtures, 8,15-18 polymers with redox-induced phase changes, 19 and supramolecular host-guest interactions 5,6,8 have shown promise for greatly altering the ΔSrc for redox couples due to the concomitant ordering or release of solvent molecules following redox reactions. Although these recent studies employ varying methods for controlling solvation entropy, few have explored increasing charge density of the electrolyte.…”
mentioning
confidence: 99%